Penanganan Hoaks Berdasarkan Hukum Adat Aceh - Muhammad Adli; S. Sulaiman (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2018)
Fraud spread in various social spaces. With the development of information and communication technology, it also accelerates the spread of false news, which must be overcome so that it does not become a serious problem in people's lives. This study wants to answer: (1) how far the hoax known in Aceh's adat law? (2) how is to handle the hoaxes using adat law perspectives in Aceh? This study aims to describe hoax context recognized in adat law in Aceh and analyze how to handle the hoaxes using adat law the perspective in Aceh community. The method used to answer the question of this study is socio-legal. The study found that the hoax is known in Aceh’s adat law. The existence of hoax can be found in the Aceh context, through various terms known locally. Handling the hoaxes is carried out by customary legal mechanisms and uses adat sanctions and is tried by adat institution functionaries. The article concludes that hoaxes are known in the local community which can be solved by traditional methods in the community itself. It is recommended that the settlement of hoaxes especially small cases, can only be used through adat law concept.